Analisis Putusan Mahkamah Agung Nomor 1644 K/Pdt/2020 Atas Perkara Ingkar Janji Menikah Sebagai Dasar Perbuatan Melawan Hukum - Wildan Sugandi; M. Yazid Fathoni (Fakultas Hukum Universitas Mataram, 2023)
This study aims are to know agreement law on propose according to Civil Law, Marriage Law, Islamic Law Compilation, indigenous law and to know ratio decidendi of supreme court verdict Number 1644 K/PDT/2020 in the case of marriage broken promises as the foundation of act against the law. Type of this research is normative legal research and applies statute, conceptual and case approaches. Result of this study shows that marriage broken promise is an act against the law which refer to Article 1365 Civil Law in general meaning. Judge consideration which used in the case Number 1644 K/PDT/2020 is interpretation on the concept of act against the law in general meaning, which including actions that against the decency and propriety in the society values. Marriage broken promise cause material and non-material loses thus in judge decision obligate the defendant to pay loses as Rp. 150.000.000,- to the plaintiff as consequences of defamation which he had done to the platiff.